Revision of the Agrilus wittemani species–group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar - Jendek, Eduard; Nakládal, Oto (Zootaxa, 2017)
The newly defined Agrilus wittemani species–group comprising six species from South and Southeast Asia is revised based on the examination of type specimens. A key to species is provided and complemented with illustrations of habitus and genitalia. The following three new species are described: Agrilus amplinotus sp. nov.; A. stigmula sp. nov.; A. stigmulifer sp. nov.